Управляемое термическое упрочнение проката - Узлов И. Г. Иван Герасимович; Парусов В.В. Владимр Васильевич; Гвоздев Р. В. Рудольф Владимирович; Филонов О. В. Олег Васильевич (Киев, Тэхника, 1989)
Авт. указаны на обороте тит. л.